The ’Right To Request’ Flexible Work In The New Zealand Public Services - Proctor-Thomson, Sarah; Donnelly, Noelle; Plimmer, Geoff (School of Management Working Papers, 2011)
Recent legislative changes within New Zealand place a duty on employers to consider flexible working requests from employees with caring responsibilities. The reshaping of working time and the provision of flexible work arrangements (FWAs), through the recently enacted „right to request‟ legislation, is designed to provide workers with greater „choices‟ about when and where they work. The provision of such flexible work choices is seen to be key in enabling workers to reconcile their working lives with their domestic responsibilities. This paper draws on large scale survey research which explores the nature of flexibility and voice exercised by women in the New Zealand public services. The findings reveal that women have influence in how they do their tasks and take their breaks but have little voice in the organisation and pace of their work. Furthermore, against a background of rising workloads and time pressures, this research highlights that the uptake of flexible work „choices‟ is increasingly difficult to access. It finds that the burden of organising FWAs, and of managing competing workload issues, is pushed down to the individual worker. In short, the research argues that the provision of FWAs in the form of „right to request‟ legislation is an exercise in certain forms of constrained „voice‟ rather than an exercise in worker „choice‟.